An Introduction to a Vygotskian Tradition: The Potential of Sociocultural Activity Theory for Studies into Cognitive Development in Islamic Education - Dery Tria Agustin (FITK UIN Walisongo, 2021)
This paper presents the potential of sociocultural activity theory as a combined theoretical and analytical framework for cognitive-developmental research in Islamic education. The paper is divided into three main sections. The first section briefly explains Vygotsky’s sociocultural theory, especially the concepts of mediation and the genetic method. The second section accounts for the related activity theory, that is, the second-generation activity theory, including the second-generation activity system model and its notion of contradiction. Drawing on a larger study into teacher cognition, the third section reports how sociocultural activity theory informed the study’s methodology, especially data collection and analysis techniques. Finally, this paper concludes with implications for future Islamic educational researchers seeking to conduct cognitive-developmental studies in their settings.